The few body problem : proceedings of the Ninth International Conference on the Few Body Problem, Eugene, Oregon, USA, 17-23 August 1980 ; plenary session papers - Levin, F. S. (Frank S.), 1933- (North Holland, 1981)
The Few Body Problem covers the proceedings of the Ninth International Conference on the Few Body Problem, held in Eugene, Oregon, USA on August 17-23, 1980. The book focuses on relativistic and particle physics, intermediate energy physics, nuclear, atomic, and molecular physics, and chemistry. The selection first offers information on nucleon-nucleon interaction in applications, including derivation of the nucleon-nucleon potential, nuclear many-body problem, and classic nuclear structure. The text also looks at three- and four-nucleon systems and graphs of three-body wave functions. The p.